Estudio de mercado para evaluar los servicios e identificar las necesidades no satisfechas de los asociados de la Cooperativa de servicios multiples de los educadores de la Región Huetar Norte R.L. Coopeande Nº7 R.L. - Alfaro-Rojas, Yinely (Instituto Tecnológico de Costa Rica, 2016)
The main objective of this marketing research is to evaluate the services provided by Cooperativa de Servicios Múltiples de los Educadores de la Región Huetar Norte R.L., known by the short name of COOPEANDE N°7 R.L., and at the same time to identify the unsatisfied needs of its associates with the purpose of creating a new portfolio of products/services and promotional strategies. The marketing research took place at the department of projects of the cooperative. The market research used a quantitative approach and it had one unique target audience: the associates of COOPEANDE N°7 R.L. The research was completed through a survey filled out by the associates themselves. The survey was implemented through a carefully structured questionnaire that yielded the necesary information to meet the objectives of the study. The research data provided information on the associate’s current level of satisfaction given the services that the cooperative provides. At the same time, it was possible to identify which products and services the cooprative can provide under the new portfolio of products and services in order to fully satisfy the needs of such associates. In addition, it was determined which are the best strategies to promote the new proposed portfolio of products and services.
Proyecto de graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2016.
Keywords: Cooperativismo; Servicios; Mercadeo; Productos